1983
DOI: 10.1002/pol.1983.170210418
|View full text |Cite
|
Sign up to set email alerts
|

Melt spinning of syndiotactic 1, 2‐polybutadiene for preparation of carbon fibers

Abstract: The thermal crosslinking and loss of vinyl unsaturation of syndiotactic 1, 2‐polybutadiene(s‐PB) at 180–230°C were prevented by stabilizers with 3, 5‐di‐t‐butyl‐4‐hydroxybenzyloxy group. The s‐PB samples (mp 140–198°C and MW 20,000–70,000) that contained the stabilizers could be melt‐spun at a temperature below 220°C into 1‐denier fibers to be used for the preparation of carbon fibers. The s‐PB fibers with higher mp and/or higher MW could be obtained by the addition of a high boiling solvent such as tetralin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Furthermore, the sequence structure and stereoisomerism of polymer were analyzed by 13 C NMR spectra (Figure 3). [30][31][32][33] The peaks around 115 and 144 ppm were assigned to the vinyl methylene and methane carbons of 1,2 unit, respectively. The chemical shifts of syndiotactic pentad rrrr were around 143.9 and 114.7 ppm, and the rrrr content ranged from 63.8 to 76.6% by increasing the monomer feed ratio.…”
Section: Synthesis and Structure Of Polymermentioning
confidence: 99%
“…Furthermore, the sequence structure and stereoisomerism of polymer were analyzed by 13 C NMR spectra (Figure 3). [30][31][32][33] The peaks around 115 and 144 ppm were assigned to the vinyl methylene and methane carbons of 1,2 unit, respectively. The chemical shifts of syndiotactic pentad rrrr were around 143.9 and 114.7 ppm, and the rrrr content ranged from 63.8 to 76.6% by increasing the monomer feed ratio.…”
Section: Synthesis and Structure Of Polymermentioning
confidence: 99%
“…6 The ratio of I B / I A increases with decreasing crystallinity, decreasing size, and increasing degree of distortion of crystallite and with lowering temperature of stretching and/or increasing stretch ratio.…”
Section: Infusibilization Dehydrogenation S-pb Fibersmentioning
confidence: 98%
“…34,35 Additionally, the catalyst system comprising cobalt salt, alkylaluminum compound, and CS 2 is known to be useful for syndiotactic-1,2-polymerization of 1,3-butadiene. [24][25][26][27] 1,4-cis-Polymerization is carried out and the reaction is stopped by adding TEA as a switching reagent. After that, the second reaction starts by adding cobalt octoate and CS 2 .…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Ashitaka et al reported on the synthesis of syndiotactic-1,2-PB (SPB). [24][25][26][27] The SPB had a 99.3% 1,2-configuration and its syndiotacticity was 99.1%. It showed high crystallinity (79%), and its T m was 206 C.…”
Section: Introductionmentioning
confidence: 99%